Management and Evolution of African Swine Fever, in Romania, during 2017-2020 - Kálmán IMRE; Sebastian-Alexandru POPA; Corina PASCU; Ionica IANCU; János DÉGI; Luminița COSTINAR; Viorel HERMAN (Communications of International Proceedings, 2021)
The paper presents the management of African Swine Fever outbreaks (ASF) in Romania, from 2017-2020. The presence of ASF in the analyzed interval decreased the total number of pigs in Romania by 16%. The disease was first diagnosed in Romania in 2017, and subsequently spread throughout the country, so that, in only 4 years, all 41 territorial administrative units were affected. During the analyzed duration, 5394 outbreaks of disease were registered, for the eradication of which 563,862 pigs (domestic and wild) were killed. In order to combat the disease, in the analyzed interval, compensations in the amount of over 100 million euros were made, granted to a number of 15,038 owners (individuals and legal entities). Although sustained efforts have been made to combat ASF, the epidemiological data collected, by the end of 2020, show that the problem of this disease is not solved, which will force Romania to continue to spend large sums of money in the fight against these diseases, for disease surveillance, killing of suspected pigs, destruction of corpses and compensation of affected owners. In addition, the trade in pig meat, products and by-products resulting from the processing of slaughtered pigs is affected for several years.
Keywords: African Swine Fever; Management; Outbreaks; Romania.